The Americanization of three African musical instruments - Murphy, Dennis (International Library of African Music, 1972)
This article describes three instruments often made and used in the United States by myself, my friends and students. These have ultimately been inspired by African instruments. Although in each instance I have developed the local variant and introduced it to others, many people have built these, and presumably have taught others to make and use them. Thus all three are now a minor part of amateur music-making in several localities in the United States
Keywords: Africa; Musical instruments; Ethnomusicology; United States; African Music